Can circulating M30 and M65 levels be beneficial markers in the diagnosis and management of patients with complete hydatidiform mole? - (:unkn) unknown (SPRINGER WIEN, 2016)
The objective of this study is to evaluate the prognostic value of M30 and M65 levels as markers of apoptotic activity and maternal serum oxidative stress in patients with complete hydatidiform mole (CHM). In total, 68 pregnant women were included in the study. The study group included 34 pregnant with CHM, while 34 healthy pregnant were employed as a control group. Venous blood samples were drawn to assess the maternal serum oxidative stress and M30-M65 levels. In addition, a second blood sample was drawn from patients with CHM on day 8 after dilatation evacuation. Maternal serum oxidative stress and M30-M65 levels were found to be significantly higher in patients with CHM as compared with the control group. It was found that serum beta-subunit of human chorionic gonadotropin (beta-hCG) level had a significant positive correlation with M30-M65 levels in patients with CHM. In addition, serum M65 level was found to be as effective as beta-hCG in the identification of the patients with CHM. Our results indicated that oxidative stress and apoptosis may play significant roles in CHM development. In addition, it seems that serum M30-M65 levels can presumably be an ancillary laboratory test to beta-hCG in the diagnosis and follow-up of the patients with CHM.
Keywords: Complete hydatidiform mole; Apoptosis; v beta-hCG; M30 level; M65 level; OXIDATIVE STRESS; SERUM M30; APOPTOSIS; VALUES; HEALTH